Helligånden, Guds røst på jord - Mortensen, Morten (Grundtvig-studier, 1977)
The Holy Spirit - God’s Voice on Earthby Morten Mortensen Few Western theologians have talked so much about the Holy Spirit as Grundtvig. When Grundtvig constantly fastens his gaze on the present reality and the presently active God, belief in the Holy Spirit acquires a particular importance. There are thus good grounds for inquiring into Grundtvig’s theology of the Holy Spirit, also since demands have been heard from several quarters in our day and age for renewed attention to be paid to the third article of the Creed.When Grundtvig wishes to explain who the Holy Spirit is, he maintains that one must first grasp what the spirit of a people is before one can understand the spirit of the people of God. This understanding is supported from the Bible by the fact that it was the Holy Spirit that in the act of creation created the human spirit as an image of itself, inasmuch as God breathed into the soil and created a human being. This human spirit is closely connected with the ability to live in a invisible world, which is held together through language and which can be passed on through words. Word and spirit belong together, says Grundtvig - the spirit is the vital force in the word. The spirit is the faith, hope and love that lie in the words.The human spirit should thus be handed down from generation to generation through the native tongue. But as a result of the Fall it was eclipsed and destroyed, so that the image of God’s Spirit became unrecognizable in it. But with Jesus, God’s Spirit came again to the human spirit. For God the Father’s Spirit was also Jesus’ Spirit, inasmuch as He was conceived by Him and walked in the Spirit. Through the atonement on the cross Jesus could then give the race of man a share in His own spirit, so that the race of man could be saved and enlightened in Him. Thus it was that on Whit Sunday the Holy Spirit could join forces with baptism and the Eucharist, since He was in “the Words of the Lord’s own mouth”. The Spirit is therefore handed down together with the visible signs from generation to generation, and must in this way pass through the generations in order to regenerate and renew the fallen human spirit. On the Day of our Lord Jesus Christ the human spirit will thus be completely one with the Holy Spirit.It is obvious that this theology of the Holy Spirit is bound up with an understanding of the Trinity which differs from the one in the orthodoxy of the Lutheran tradition. Thus Grundtvig stresses the threeness in the Trinity of the Godhead and emphasizes in particular that the Spirit is a person. In this emphasis on the threeness he shows a dependent position on the Eastern one, which is also revealed in the fact that the Spirit is not said to emanate from the Father and the Son, but is said to emanate from the Father through the Son.This inquiry thus points out how Grundtvig really manages to talk about the presence of God. He can do so by virtue of a profound understanding of the person of the Holy Spirit.